Comparative Study of Various Human Ossification Centers From 10 Years to 20 Years of Age - Y.V.Ratna Raju; M. Rajeev Varma; Raja sekhar Uppu; P Vijaya Kumar (Indian Journal of Forensic Medicine & Toxicology, 2022)
Introduction: The appearance and fusion of different ossification centers has a sequence. The processof union of epiphysis and diaphysis is called fusion and the fusion is a process, not an event. This studyis an attempt to compare various human ossification centers radiologically in both males and femalesfor estimation of age.Materials and Methods: This is a retrospective study based on the radiological findings from the casesreferred to the Dept of forensic medicine, Rangaraya medical college, Kakinada. X-rays of shoulder,elbow, wrist and pelvis are utilized for this study. Age range of cases we studied was 10-20yrs of age.Ossification centers for upper end of humerus, medial epicondyle, upper end of radius, lower endof ulna, lower end of radius, pisiform, base of first metacarpal, iliac crest, femur head and greatertrochanter were studied in relation to each other. The ossification process is divided into 7 progressivestages (0-6) based on the stage of appearance and fusion of the ossification centers. Master charts wereprepared for boys and girls separately and analyzed.Results and Conclusion: Radiological findings of shoulder, elbow, wrist and pelvis from a total of 109belonging to the females and 40 belonging to the males were studied and a point score taking Gray’sanatomy as standard and making correction for Indians is given to the 10 ossification centers studied. Itis found that with increasing age the point score is increasing. It is found that the point score in femalesis higher than in males at a given age in majority of cases indicating ossification process concludingearly in females than in males.